Description of a new leech species of Helobdella (Clitellata: Glossiphoniidae) from Mexico with a review of Mexican congeners and a taxonomic key - Salas-Montiel, Ricardo; Phillips, Anna J.; de Leon, Gerardo Perez-Ponce; Oceguera-Figueroa, Alejandro (Zootaxa, 2014)
To date, six species of the leech genus Helobdella have been recorded from Mexico: Helobdella atli, Helobdella elongata, Helobdella octatestisaca, Helobdella socimulcensis, Helobdella virginiae and Helobdella temiscoensis n. sp. This new species is characterized by a lanceolate body, the presence of a nuchal scute, uniform brown pigment on both dorsal and ventral surfaces, the absence of papillae, well-separated eyespots, six pairs of testisacs and five pairs of crop caeca, the last of which forms posterior caeca. In addition, we provide new geographic records for Helobdella species from Mexico resulting from our own collections, vouchers deposited at the Colección Nacional de Helmintos from the Instituto de Biología, UNAM, Mexico and vouchers at the Invertebrate Zoology Collection of the Smithsonian’s National Museum of Natural History (USNM) Washington D.C., USA. We present a comprehensive review of Mexican Helobdella species, including the new species, with notes on the characteristic morphology and geographic distribution of each species with 91 new records from 20 states. In addition, we provide a taxonomic key for the identification of the Mexican species.